SUBJECTIVE POSITION FORMATION OF THE MEDICAL UNIVERSITY STUDENTS - T. V. Kalmykova (Медицинский вестник Юга России, 2014)
The idea of development and self-development of subjectivity permeates the National doctrine of education in the Russian Federation up to 2025. Stresses the need for the mobilization of personal potential, integrity preservation, reproduction in every person’s quality of subjectivity. The challenge of education is to create the condition for gaining medical student personal meaning, values and goals of its development. The real result of education in these conditions is the development of the ability of medical students (future professional) to feel the way in changing the world and oneself as a part of this world, the willingness to meet with surprises and ability to respond to these meetings a positive innovation.